DEVELOPMENT OF A ROCKET COOK STOVE WITH A FRUSTUM CHAMBER AND HEAT EXCHANGER - Mondejar, Jeremy P (Journal of Agriculture and Technology Management, 2008)
The main goal of this study is to develop an improved cooking stove that reduces the pressurplaced on local forests by reducing the amount of wood the stoves consume. A rocket cookstove with a frustum chamber and a heat exchanger was designed, fabricated and evaluated. It is made of 0.8mm G.I. sheet and weighs about 2.9 kg. The rocket cookstove have four separable parts (1) the firewood shelf, (2) frustum chamber, (3) body, and (4) heat exchanger. The performance of the cookstoves was determined by a Water Boiling Test (WBT). A rocket cookstove with a frustum chamber and a heat exchanger performs best among the three cookstoves. The time required to boil 5 liters of water from a cold-start and a hot-start high-power tests by a rocket stove with the heat exchanger were about 24 and 19 minutes, respectively. These were significantly shorter at 5% level of significance compared to the rocket stove without heat exchanger exhibiting about 28 and 25 minutes, respectively; and to the traditional open-air stove requiring about 36 and 29 minutes, correspondingly. As a result, the specific consumption of the rocket cookstove with a frustum chamber and a heat exchanger was significantly lower by about 50% during the cold-start high-power test and about 60% during the hot-start highpower test. The design of this improved rocket cookstove with a frustum chamber and a heat exchanger reveals a significant advantage over the traditional open-air stove. Hence, using this type of stove, the wood consumption for cooking and heating can be reduced by as much as 50% as consumed by the traditional open-air stove. Furthermore, this can alleviate the pressure on local forests and can reduced risk on health of man and the environment.